KETERKAITAN PENGGUNAAN MOVING CLASS DENGAN MOTIVASI BELAJAR DAN DAMPAKNYA TERHADAP KEPUASAN BELAJAR EKONOMI SISWA MAN 2 MODEL PEKANBARU - Ekwanis Putrielis (Program Studi Pendidikan Ekonomi Universitas Riau, 2017)
This research is purpose to know relation the using of moving class with studentmotivation and the impact to satisfaction to the economic lesson of student MAN 2Model Pekanbaru. This ressearch method is using descriptive researching withquality closing. This research population is used of students in grade eleventh andtwelveth social about onw hundred and two peoples,by types about 80 peoples thatchoosed randomly by using minimum types. Taking the data is done by analisymand spreading (angket) research to the respondent. This data analys with twiceanalisysm regration.Facing research instrument used an analisym uses testing thevalidity and reliability with using the formula of “alpha cronbach “. This researchshown where : (1) There are have significant relationship with studying facilities thatused inmoving class to the satisfication studying by studying motivation. (2)There isno significant relationship the quality of the teachers in studying process by movingclass system with satisfication of students by studying motivation. (3) There is nosignificant relationship the studying source with satisfication of students. By theresearch above we can solve that the studying satisfication by studying motivationcan get if the teachers really done the lesson process by moving class, and shouldbe looked the studying source that usefull. And in this case should be increase sothe studying purpose by using moving class system done goodly.